Representações Sociais de Carreira: um Estudo Com Profissionais de Diferentes Idades - Sabadini, Greice (2020)
This research aims to investigate and analyze the formation and structure of social representations of career for professionals of different ages in the business area. The study was carried out in a sample of 190 young professionals, from 18 to 29 years o